Mnemotechnical Strategy in Learning the German Language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article discusses the possibility of using mnemotechnical strategies in learning the German language. The focus is on the definition of "mnemotechnical strategy" are considered mnemotechnical means teaching of the German language and the possibility of using mnemotechnical strategies in the process of assimilation of lexical and grammatical phenomena.
Keywords: mnemotechnical strategy; mnemotechnical means; learning the German language